Time-of-Flight Secondary Ion Mass Spectrometry based Molecular Histology of Human Spinal Cord Tissue and Motor Neurons - Hanrieder, Jörg (2013)
Secondary ion mass spectrometry is a powerful method for imaging biological samples with high spatial resolution. Whole section ToF SIMS scans and multivariate data analysis have been performed on human spinal cord in order to delineate anatomical regions of interest based on their chemical distribution pattern. ToF SIMS analysis of thoracic spinal cord sections was performed at 5µm resolution within 2 hours. Multivariate image analysis by means of principal component analysis and maximum auto correlation factor analysis resulted in detection of more than 400 m/z peaks that were found to be significantly changed. Here, the results show characteristic biochemical distributions that are well in line with major histological regions, including grey and white matter. As an approach for iterative segmentation, we further evaluated previously outlined regions of interest as identified by multivariate image analysis. Here, further discrimination of the grey matter into ventral, lateral and dorsal neuroanatomical regions was observed. TOF SIMS imaging has been carried out at submicron resolution obtaining localization and characterization of spinal motor neurons based on their chemical fingerprint, including neurotransmitter precursors that serve as molecular indicators for motor neuron integrity. Thus, TOF SIMS can be used as an approach for chemical histology and pathology. SIMS holds immense potential for investigating the subcellular mechanisms underlying spinal cord related diseases including chronic pain and amyotrophic lateral sclerosis.